Evidence for the anti-inflammatory activity of Bupleurum marginatum (Apiaceae) extracts using in vitro and in vivo experiments supported by virtual screening - Ashour, Mohamed L.; Youssef, Fadia S.; Gad, Haidy A.; Readi, Mahmoud Zaki el; Bouzabata, Amel; Abuzeid, Riham M.; Sobeh, Mansour; Wink, Michael (Journal of pharmacy and pharmacology, 2018)
Objectives To explore the potential anti-inflammatory activity of Bupleurum marginatum extracts using in vitro and in vivo studies supported by virtual screening. Methods Antioxidant activity was assessed using the DPPH˙ and inhibition of 2-deoxyribose degradation assays. Anti-inflammatory activity was determined in vitro by measuring the suppression of prostaglandin E2 release (PGE2) in pancreatic cancer cells (MIA-PaCa-2) and the inhibition of 5-lipoxygenase whereas the rat paw oedema was used in vivo. The major constituents were docked in 5-lipoxygenase and cyclooxygenase-II active sites. Key findings Methanol and dichloromethane (DCM) extracts showed IC50 of 46.99 and 162.99 μg/ml in the DPPH˙, 1.52 and 2.12 μg/ml in inhibition of 2-deoxyribose degradation assays, respectively. They reduced PGE2 release by 41.33 and 52.85% at 25 μg/ml and inhibited 5-lipoxygenase with IC50 of 45.28 and 25.92 μg/ml, respectively. 50 and 70% reduction in the diameter of the carrageenan-induced rat paws with methanol and DCM extracts, respectively, with a marked decline in the inflammation score was observed. Rutin, a predominating compound, showed a strong interaction with the key amino acids in 5-LOX active site with interaction energy of −74.59 kcal/mol. Conclusions Our study provides evidence for an interesting anti-inflammatory activity of B. marginatum aerial parts offering a natural anti-inflammatory agent.
Gesehen am 08.06.2020